THU0276 A randomized, open-label study to explore whether partial remission can be maintained with naproxen or no treatment in patients with early, active axial spondyloarthritis: Preliminary results of INFAST part II. (23rd January 2014) - Sieper, J.; Lenaerts, J.; Wollenhaupt, J.; Mazurov, V.I.; Myasoutova, L.; Park, S.-H.; Song, Y.-W.; Yao, R.; Chitkara, D.; Vastesaeger, N.
Abstract : Background: In patients with axial spondyloarthritis (SpA) who have achieved partial remission, it is unclear whether continuous treatment with NSAIDs is superior to stopping treatment. Objectives: To investigate whether continued treatment with naproxen (NPX) was superior to discontinuing all treatment in order to maintain disease control for 6 months in early, active axial SpA patients who were in partial remission after 28 weeks of therapy with either infliximab (IFX)+NPX or placebo+NPX. Methods: Part I of INFAST was a double-blind, randomized controlled trial of IFX in biologic-naïve patients 18–48 years of age with early, active axial SpA. Patients were randomized (2:1) to receive 28 weeks of treatment with either IV IFX 5 mg/kg (weeks 0, 2, 6, 12, 18, and 24)+NPX 1000 mg/d or IV placebo+NPX 1000 mg/d. In Part II of INFAST, patients who had achieved Assessment in Ankylosing Spondylitis (ASAS) partial remission at week 28 continued in Part II of the study with no IFX treatment. These patients were randomized in a 1:1 ratio to continue on NPX or to stop NPX until week 52. Patients from the 2 treatment arms in Part I were equally balanced over the 2 groups in Part II. The outcome explored was the proportion of subjects who maintained ASAS partial remission at week 52; detection of a treatment group difference in this small sample size would require large differences (>40%) for statistical significance. Treatment group differences were analyzed using Fisher exact tests. MRIs of spine and sacroiliac (SI) joints at baseline (week 28) and week 52 were used to assess inflammation. Patients with flares (BASDAI ≥30 mm [on a 100 mm VAS] during 2 consecutive visits within 1–3 weeks) had a final MRI and were discontinued. Results: In preliminary results, 41 patients were randomized to NPX and 41 to no treatment in Part II of INFAST. Mean BASDAI scores at the start of follow-up were 7.1 (SD=6.63) mm and 6.2 (SD=6.99) mm in the NPX and no-treatment groups, respectively. At week 52, similar numbers of patients in the NPX group (19/40, 47.5%) and the no-treatment group (16/40, 40.0%) met the ASAS partial remission criteria, P =0.6525. Complete absence of lesions on MRI was achieved by similar numbers of patients in the NPX and no-treatment groups for combined spine and SI lesions (2.5% vs 2.5%), SI lesions alone (7.5% vs 10.0%), and spine lesions alone (50.0% vs 40.0%), all P >0.5. Few flares were experienced by patients during follow-up treatment (NPX, 1/40, 2.5% vs no treatment, 3/40, 7.5%; P =0.6153). During the follow-up period, 1 serious adverse event was reported in the no-treatment group. No deaths occurred. Conclusions: ASAS partial remission was maintained at week 52 by 47.5% of patients who stayed on NPX therapy and 40.0% of patients in whom all treatment (IFX and NPX) was stopped. Disclosure of Interest: J. Sieper Grant/Research support from: Merck, Abbott, Pfizer, Consultant for: Merck, Abbott, Pfizer, UCB, Roche, Lilly, Speakers Bureau: Merck, Abbott, Pfizer, J. Lenaerts Consultant for: Abbott, BMS, MSD, Pfizer, Roche, Astra Zeneca, J. Wollenhaupt: None Declared, V. Mazurov: None Declared, L. Myasoutova: None Declared, S.-H. Park: None Declared, Y.-W. Song: None Declared, R. Yao Employee of: Merck, D. Chitkara Employee of: Merck, N. Vastesaeger Employee of: Merck